Cloning, purification, crystallization and preliminary structural studies of penicillin V acylase from Bacillus subtilis - Rathinaswamy, P.; Pundle, A. V.; Prabhune, Asmita; SivaRaman, H.; Brannigan, James A.; Dodson, Guy G.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology Communications, 2005)
{Penicillin acylase proteins are amidohydrolase enzymes that cleave penicillins at the amide bond connecting the side chain to their beta-lactam nucleus. An unannotated protein from Bacillus subtilis has been expressed in Escherichia coli, purified and confirmed to possess penicillin V acylase activity. The protein was crystallized using the hanging-drop vapour-diffusion method from a solution containing 4 M sodium formate in 100 mM Tris-HCl buffer pH 8.2. Diffraction data were collected under cryogenic conditions to a spacing of 2.5 A. The crystals belonged to the orthorhombic space group C222(1), with unit-cell parameters a = 111.0

Tryptophan residue is identified in the substrate binding of penicillin G acylase from Kluyvera citrophila - Kumar, R. Suresh; Prabhune, Asmita; Pundle, A. V.; Karthikeyan, Muthukumarasamy; Suresh, C. G. (Enzyme and Microbial Technology, 2007)
Penicillin acylases are important enzymes in pharmaceutical industry for the production of semi-synthetic beta-lactam antibiotics via the key intermediate 6-aminopenicillanic acid. The penicillin G acylase purified from Kluyvera citrophila (KcPGA) on modification with tryptophan-specific reagents such as N-bromo succinamide (NBS) and 2-hydroxy 5-nitrobenzylbromide (HNBB) showed partial loss of activity and substrate protection. Various solute quenchers and substrate were used to probe the microenvironment of the putative reactive tryptophan through fluorescence quenching. Homology modeling of KcPGA structure has been carried out. Docking substrate on this modeled KcPGA structure identifies the tryptophan residue that is directly influenced by substrate binding. To confirm the biological significance of this particular tryptophan, we did a sequence comparison of PGAs from various organisms. The sequence alignment clustered the matches into two sets, those closer to (> 40% identical) KcPGA and had the tryptophan of interest present in them formed the first set, while those less identical (< 30%) to KcPGA and the particular tryptophan absent in them formed the second set. It is clear from the reported kinetic parameters of representative members of these two sets that the affinity for penicillin G (penG) of the former class is several times better. Thus, based on our studies we suggest that the tryptophan residue in the identified position is important for binding substrate penG by the acylases. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: fluorescence measurement; K. citrophila; Penicillin G acylase; sequence alignment; substrate-docking; tryptophan modification

Molecular features of bile salt hydrolases and relevance in human health - Chand, D.; Avinash, V. S.; Yadav, Y.; Pundle, A. V.; Suresh, C. G.; Ramasamy, S. (Biochimica et Biophysica Acta - General Subjects, 2017)
Background: Bile salt hydrolase (BSH) enzyme is responsible for the de-conjugation of bile salts by commensal bacteria, thus playing a vital role in their colonization and survival in the mammalian intestine and determination of their probiotic potential. Further, bile deconjugation also leads to lowering of cholesterol and alterations in energy homeostasis, thus making BSH a clinically important enzyme. Scope of the review: Many recent observations have indicated that BSH may be involved in a multifaceted array of roles, directly or indirectly in the host and microbial physiology. BSH paralogues have now been found to occur in different microbes including free-living and pathogenic bacteria and Archaea. BSHs from various sources also show differential activity and substrate spectrum. Certain bacteria are known to possess multiple genes for BSH enzymes. BSHs have been reported to influence different metabolic phenomena, including bacterial pathogenesis and the maintenance of lipid and glucose homeostasis in the host. These observations necessitate an intense study into the biochemical, structural and regulatory features of BSH enzymes to better understand their role in regulating bacterial and host metabolism. Major conclusions: In this review, the available information on the characteristics of BSH enzymes have been organized in order to understand their interactions with a wide range of substrates and their myriad physiological roles, from bile resistance to signalling mechanisms. General significance: A detailed exploration of BSH architecture and regulation could provide insights into its evolution and a deeper appreciation of the multiple functions of this enzyme relevant to healthcare.